Submerged Glow-Discharge Plasma: An Economical Approach to Convert Construction Scrap Metal into Nanomaterials - Yek Peter Nai Yuh; Julaihi Muhammad Rafiq Mirza; Osman Mohammad Shahril; Tiong Tung Chuan; Lee Wak Ha; Lee Chern Leing (E3S Web of Conferences, 2018)
Submerged glow-discharge plasma (SGDP) is relatively new among the various methods available for nanomaterials synthesis (NMs) techniques. This method allows great control over the production cost of nanomaterials synthesis. A lab-scale batch type SDGP technology has been constructed to produce nanomaterials and investigate the inter-relationship between plasma excitation voltages, electrodes submerged areas and electrolyte concentration. Metal oxide nanospheres has been synthesised from different electrolyte concentrations (1M-0.001M) and characterized by Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). As the major results showed that the nanospheres are uniformly spherical with diameter size distribution are between 100 nm - 2μm. EDS analysis shown the nano-Iron Oxide have been formed. Scrap metal initially showed around 6.45% and 93.55% of Carbon and Iron composition respectively. After SGDP process to the scrap metal, Carbon content has increased to 34-35% and Iron content has reduced to around 15-40%. EDS results also shown the higher percentage of Iron amount has remained with lower electrolyte concentration and Current is proportionally related to submersion area of cathode.